2022
DOI: 10.1152/ajpregu.00140.2021
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 deficiency attenuates lipopolysaccharide-induced inflammation, apoptosis, and acute lung injury in adult mice

Abstract: Many lung diseases are caused by an excessive inflammatory response, and inflammatory lung diseases are often modeled using lipopolysaccharide (LPS) in mice. Cyclooxygenase-2 (COX-2) encoded by the Ptgs2 gene is induced in response to inflammatory stimuli including lipopolysaccharide (LPS). The objective of this study was to test the hypothesis that mice deficient in COX-2 (Ptgs2-/-) will be protected from LPS-induced lung injury. Wild type (WT, CD1 mice) and Ptgs2-/- mice (on a CD1 background) were treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…[13][14][15] LPS activates a large number of inflammatory cells and induces pneumonia through a variety of signaling pathways. [16][17][18] In this study, we successfully constructed a pneumonia model using LPS, and confirmed the effects of GPF on this model.…”
Section: Gpf Could Improve Lps-treated Beas-2b Cell Viabilitysupporting
confidence: 61%
“…[13][14][15] LPS activates a large number of inflammatory cells and induces pneumonia through a variety of signaling pathways. [16][17][18] In this study, we successfully constructed a pneumonia model using LPS, and confirmed the effects of GPF on this model.…”
Section: Gpf Could Improve Lps-treated Beas-2b Cell Viabilitysupporting
confidence: 61%
“…PTGS2, also known as cyclooxygenase, can catalyze AA to generate PGs, which are mainly involved in inflammation, cell proliferation and apoptosis. In addition, PTGS1 can regulate angiogenesis in endothelial cells [ 51 ]. PLA2G1B is a phospholipase A2 that catalyzes membrane glycerophospholipids to release AA and Lys phospholipids, which are involved in cell contraction and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…These three pathways of AA were closely related to lung injury. Mice deficient in COX-2 could attenuate LPS-induced inflammatory response and the resultant acute lung injury by regulation of LPS-induced levels of cytokines/chemokines ( Nelin et al, 2022 ). 12/15-LOX was shown to be involved in the regulation of eicosanoid production in the respiratory system using knockout mice model.…”
Section: Discussionmentioning
confidence: 99%